Band gap engineering of a MoS2 monolayer through oxygen alloying: an ab initio study. (9th October 2018) - Andriambelaza, N F; Mapasha, R E; Chetty, N
Abstract: Oxygen (O) alloying in a MoS2 monolayer appearing in different shapes: line-ordered, cluster and random have been theoretically designed, for band gap engineering in order to extend its nanotechnological applications. The thermodynamic stability, structural and electronic properties of these alloy configurations at each concentration have been comparatively studied using the density functional theory methods. Based on the formation energy analysis, the O line-ordered alloys are most stable compared to the well known random and cluster alloys at high concentration, while at low concentration they compete. The lattice constants of all the alloyed systems decrease linearly with the increase in O concentration, consistent with Vegard' s law. The Mo–O bond lengths are shorter than Mo–S leading to a reduction in the band gap, based on density of state analysis. The partial charge density reconciling with the partial density of states analysis reveals that the band gap reduction is mainly contributed by the Mo 4 d and O 2 p orbitals as shown at the band edges of the density of states plots. Creation of stacking of MoS2 with MoO2 gives metallic character, with Mo 4 d orbital crossing the Fermi level. The O alloys in a MoS2 monolayer should be considered to be an effective way to engineer the band gap for designing new nanoelectronic devices with novel performance.